2019
DOI: 10.1097/phm.0000000000001371
|View full text |Cite
|
Sign up to set email alerts
|

Resilience After Spinal Cord Injury

Abstract: Provide a structured summary that includes (as applicable): background, objectives, eligibility criteria, sources of evidence, charting methods, results, and conclusions that relate to the review questions and objectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 88 publications
0
26
0
Order By: Relevance
“…Over time, those who consider injury a challenge to be overcome and who use coping skills—both inherent and learned—have a higher likelihood of recovery ( Bonanno et al, 2012 ; Kornhaber et al, 2018 ; Machida et al, 2013 ). It has been shown that exhibiting resilience is predictive of psychological, physiological, and sociological wellness among those with a sudden injury or accident such as a spinal-cord injury ( McDonald et al, 2019 ). Some of these learned behaviors include mood management, not just physical recovery ( Kilic et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over time, those who consider injury a challenge to be overcome and who use coping skills—both inherent and learned—have a higher likelihood of recovery ( Bonanno et al, 2012 ; Kornhaber et al, 2018 ; Machida et al, 2013 ). It has been shown that exhibiting resilience is predictive of psychological, physiological, and sociological wellness among those with a sudden injury or accident such as a spinal-cord injury ( McDonald et al, 2019 ). Some of these learned behaviors include mood management, not just physical recovery ( Kilic et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some of these learned behaviors include mood management, not just physical recovery ( Kilic et al, 2013 ). One of the most pertinent compensatory coping-concept strategies for those with a sudden illness or injury is optimism ( Edward, 2013 ; McDonald et al, 2019 ; Stewart & Yuen, 2011 ; Wagnild, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another article from the AJPMR journal is Resilience After Spinal Cord Injury, A Scoping Review. 29 The focus of the review is communicated clearly in the title. The population is persons with spinal cord injury.…”
Section: Examples Of Scoping Reviews From the Pmandr Literaturementioning
confidence: 99%
“…and What themes are associated with resilient outcomes? 29 As authors work to develop and conduct their reviews, the five ScR stages presented in Table 2 should be followed. The following are two recently published ScRs that clearly illustrate the process.…”
Section: Examples Of Scoping Reviews From the Pmandr Literaturementioning
confidence: 99%